2000
DOI: 10.3758/bf03200798
|View full text |Cite
|
Sign up to set email alerts
|

Living together, feeding apart: How to measure individual food consumption in social house mice

Abstract: In many studies with animals kept in groups, scientists need information about each individual's food access without disturbance or separation of the animals. We developed an automatic feeding device that allows measurement of individual food consumption and experimental manipulation of individual food availability in small social mammals, such as house mice. The feeding device is based on radio frequency identification that triggers access to a motor-driven metal arm filled with food pellets and is mediated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Experimental approaches for quantifying food intake in group-housed rodents have made progress with RFID technology. In 2000, a research group first demonstrated the potential for using implantable RFID chips to identify rodents for the purpose of scoring feeding behaviors (Neuhausser-Wespy and Konig, 2000). Another group followed up on their approach, demonstrating a highly accurate system using RFID identification for monitoring feeding of rats from a pellet dispenser (Holley et al, 2003).…”
Section: Future Directionsmentioning
confidence: 99%
“…Experimental approaches for quantifying food intake in group-housed rodents have made progress with RFID technology. In 2000, a research group first demonstrated the potential for using implantable RFID chips to identify rodents for the purpose of scoring feeding behaviors (Neuhausser-Wespy and Konig, 2000). Another group followed up on their approach, demonstrating a highly accurate system using RFID identification for monitoring feeding of rats from a pellet dispenser (Holley et al, 2003).…”
Section: Future Directionsmentioning
confidence: 99%
“…Daily food consumption of females was measured from day 2 until day 13 of lactation with the help of an automatic feeding device (Neuhäusser-Wespy & König 2000). This device allows measuring individual food consumption of group-living animals without any disturbance.…”
mentioning
confidence: 99%